Cuidados paliativos em um hospital universitário: a percepção dos profissionais de saúde, gestores e docentes - Paiva, Claudia do Nascimento (2019)
The palliative care approach promotes quality of life of patients and their families when diagnosed with life-threatening diseases; it aims to control pain, relieve symptoms and the need for care in several aspects. Although the knowledge about palliative care has been growing among health professionals, there are still certain challenges for patients to have access to the dignified service to which everyone is entitled. The general objective of this study was to understand the perception and practice of health professionals about the approach to palliative care in a university hospital. As for the specific ones, they are related to the identification of practical aspects in the provision of palliative care, as well as to verify the training and contents on palliative care offered in the researched courses. The study was developed through field research; the participants were: members of the reference and matrix team, managers and teachers of the University Hospital of a federal university, totaling 37 professionals. A questionnaire was used as research instruments to collect personal and professional data of the participants and semi-structured interviews with questions related to the theme. The data were analyzed by means of content analysis technique in the thematic modality. There were different understandings among the participants, there are those who understand that palliative care should be offered from the diagnosis of an incurable disease, contemplating the completeness of care (biopsychosocial and spiritual dimensions), in addition to the total control of pain and symptoms, prioritizing measures of comfort, through a multidisciplinary team and others who correlated the care as exclusive to patients at the end of life. The participants described the practice of palliative care in the service as something unstructured that still needs to be reflected, planned and systematized to be effectively implemented. They also highlighted the importance of the theme in the training of students in the health area. It is concluded that there is a need to improve the care to patients in palliative care through the qualification/training of the team and management support.